2003
DOI: 10.1046/j.1474-9728.2003.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed behavioural aging and altered mortality in Drosophilaβ integrin mutants

Abstract: SummaryThe genetic basis for aging is being intensely investigated in a variety of model systems. Much of the focus in Drosophila has been on the molecular-genetic determinants of lifespan, whereas the molecular-genetic basis for age-related functional declines has been less vigorously explored. We evaluated behavioural aging and lifespan in flies harbouring loss-of-function mutations in myospheroid , the gene that encodes β β β β PS, a β β β β integrin. Integrins are adhesion molecules that regulate a number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 37 publications
5
53
0
1
Order By: Relevance
“…The studies reported here, in conjunction with previous work from our group (Goddeeris et al 2003;Gargano et al 2005) and others (Miquel et al 1976;Arking and Wells 1990;Chavous et al 2001;Mockett et al 2001;Kang et al 2002;Ruan et al 2002;Morrow et al 2004;Simon et al 2006), indicate that locomotor senescence might be mechanistically connected to life span in Drosophila; i.e. long-lived flies tend to have better locomotor function across age.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The studies reported here, in conjunction with previous work from our group (Goddeeris et al 2003;Gargano et al 2005) and others (Miquel et al 1976;Arking and Wells 1990;Chavous et al 2001;Mockett et al 2001;Kang et al 2002;Ruan et al 2002;Morrow et al 2004;Simon et al 2006), indicate that locomotor senescence might be mechanistically connected to life span in Drosophila; i.e. long-lived flies tend to have better locomotor function across age.…”
Section: Discussionsupporting
confidence: 77%
“…Negative geotaxis (startleinduced vertical movement) is a frequently used index of locomotor behavior in flies (Miquel et al 1976;Arking and Wells 1990;Chavous et al 2001;Mockett et al 2001;Kang et al 2002;Ruan et al 2002;Goddeeris et al 2003;Morrow et al 2004;Gargano et al 2005;Simon et al 2006).Despite being commonly assessed, it was previously unclear whether negative geotaxis is principally a climbing behavior or a combination of climbing and other behaviors such as jumping and flying. Additionally, it was previously unclear whether age-related impairment in negative geotaxis is due to a decreased speed of vertical movement, an increased latency to initiate vertical movement, or other age-related behavioral changes.…”
Section: Introductionmentioning
confidence: 99%
“…1A). The control data are derived from our previously published studies on senescence of negative geotaxis in wild-type flies (Goddeeris et al ., 2003). The divergent, convergent and parallel data sets are hypothetical; they were designed to represent three major types of actual results that might be consistent with ameliorated functional senescence as compared with the control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The parallel group had elevated negative geotaxis scores at all ages so that its curve was parallel to control. Although statistical tests such as analysis of variance ( ANOVA ) can be used to compare overall function across age in data sets like these (e.g Goddeeris et al ., 2003), this approach leaves several questions unanswered, including: (1) Does the rate of functional decline differ between the data sets? (2) Is the time to onset of functional decline changed?…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation